2016
DOI: 10.3109/02688697.2015.1119242
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 5-ALA and iMRI in re-resection of recurrent glioblastoma

Abstract: Background Tumour resection plays a role in the initial treatment but also in the setting of recurrent glioblastoma (rGBM). To achieve maximum resection, 5-aminolevulinic acid (5-ALA) and intraoperative MRI (iMRI) are used as surgical tools. Aiming at complete tumour re-resection, we started combining iMRI with 5-ALA to find out if this leads to better surgical results. Methods We performed tumour resections in seven patients with rGBM, combining 5-ALA (20 mg/kg bodyweight) with iMRI (0.15 T). Radiologically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Sixty-four studies describe the clinical use of fluorescent agents [1, 3, 5, 6, 9, 11, 13–16, 2226, 2831, 3335, 37, 38, 4042, 44, 49, 5254, 58, 6466, 69, 71, 74, 75, 78, 8082, 8487, 89, 92, 94, 97101, 105–107, 109, 110, 113, 115, 118]. Three ways of labeling tumor cells were identified in the literature: (1) passive, (2) metabolic, and (3) molecular labeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-four studies describe the clinical use of fluorescent agents [1, 3, 5, 6, 9, 11, 13–16, 2226, 2831, 3335, 37, 38, 4042, 44, 49, 5254, 58, 6466, 69, 71, 74, 75, 78, 8082, 8487, 89, 92, 94, 97101, 105–107, 109, 110, 113, 115, 118]. Three ways of labeling tumor cells were identified in the literature: (1) passive, (2) metabolic, and (3) molecular labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-four clinical studies described the use of 5-ALA for glioma surgery [3, 5, 6, 13–16, 22, 2426, 28, 30, 31, 33, 34, 37, 4042, 44, 66, 69, 74, 75, 78, 81, 82, 84, 85, 87, 89, 94, 97101, 105, 106, 109, 110, 113, 115], of which only six studies included LGGs [28, 33, 84, 109, 110, 113]. 5-ALA is the only fluorescent agent that has been tested in an RCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Newer studies have demonstrated 5-ALA FGS combined with intraoperative MRI may be beneficial in maximizing resection of GBM. 35,36 This combination presents a potential solution to the problem encountered with 5-ALA in that not all GBM tissue uniformly exhibits 5-ALA fluorescence. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Novel resection techniques are also being explored to improve the rate of complete resection. For example, protoporphyrin IX (PpIX) is a fluorescent compound that preferentially concentrates in malignant glioma cells, allowing for successful intra-operative tumor visualization to guide surgical resection (10,11). Despite such advances, the principle of maximum safe resection is not always optimal in the setting of recurrent GBM, as the benefit of reoperation remains in question (12)(13)(14).…”
Section: Summary Of Non-rt Options For Recurrent Glioblastomamentioning
confidence: 99%